Use of fibular bone graft and cancellous screw fixation in the management of neglected femur neck fractures in young patients - Kaim Khani, Ghulam Mustafa; Hafeez, Kamran; Bux, Muhammad; Rasheed, Nusrat; Ahmed, Naveed; Anjum, M. Perwez (International Journal of Health Sciences, 2017)
Objective: To present the clinical outcome of patients with neglected femur neck fracture treated with fibular bone graft. Methods: During May 2010-February 2013, 15 patients younger than 35 years of age with neglected fracture neck of femur were managed with non-vascularized fibular graft and cannulated screws. Fractures were classified according to Sandhu Classification. Hip function was assessed using Harris hip score. Results: Fifteen patients with mean age of 28.67 years were managed. Mean period of delay from injury to presentation was 3.07 months. Mean follow-up was 18.5 months. Union was achieved in 13 cases. 2 patients developed nonunion with progression of avascular necrosis (AVN). Patients with healed fracture did not show radiological signs of AVN till the past follow-up. Functional status was evaluated at 6 months according to Harris hip score and was poor in 2 patients, fair in 2 patients, good in 6 patients, and excellent in 5 patients. Conclusion: Fibular graft along with two cancellous screws proved to be an effective technique in our cases with neglected femur neck fractures.